Persepsi Guru PAUD Tentang Program Keprofesian Berkelanjutan (PKB): Studi Kasus di Lembaga TK Islam Fatmawati - Nuria, Anniska; Utoyo, Setiyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to understand and explore teachers' perspectives regarding the Sustainable Professional Development Program (PKB), with a case study at the Islamic Kindergarten Fatmawati in the city of Jambi. The approach used is qualitative descriptive with a case study design. Data were collected through interviews using a digital questionnaire distributed via Google Forms through social media WhatsApp. The subjects of the study include all teachers at the Islamic Kindergarten Fatmawati, with a total of three respondents. The research results show that teachers understand the importance of the PKB Program as a means to continuously improve their competencies and professionalism. Teachers are aware that active participation in PKB supports the enhancement of learning quality, encourages innovation in teaching practices, and strengthens commitment to the profession. Nevertheless, teachers also face challenges such as time limitations and supporting resources to participate optimally in the program.